Impulsive Fractional Semilinear Integrodifferential Equations with Nonlocal Conditions - Xue Wang; Bo Zhu (Journal of Function Spaces)
This paper is devoted to a class of impulsive fractional semilinear integrodifferential equations with nonlocal initial conditions. Based on the semigroup theory and some fixed point theorems, the existence theory of PC-mild solutions is established under the condition of compact resolvent operator. Furthermore, the uniqueness of PC-mild solutions is proved in the case of the noncompact resolvent operator.